Ethanol-Dependent Synthesis of Salsolinol in the Posterior Ventral Tegmental Area as Key Mechanism of Ethanol’s Action on Mesolimbic Dopamine - Bassareo, Valentina; Frau, Roberto; Maccioni, Riccardo; Caboni, Pierluigi; Manis, Cristina; Peana, Alessandra T.; Migheli, Rossana; Porru, Simona; Acquas, Elio (Frontiers in Neuroscience, 2021)
Abnormal consumption of ethanol, the ingredient responsible for alcoholic drinks’ addictive liability, causes millions of deaths yearly. Ethanol’s addictive potential is triggered through activation, by a still unknown mechanism, of the mesolimbic dopamine (DA) system, part of a key motivation circuit, DA neurons in the posterior ventral tegmental area (pVTA) projecting to ipsilateral nucleus accumbens shell (AcbSh). The present in-vivo brain microdialysis study, in dually-implanted rats in one pVTA and in the ipsilateral or contralateral AcbSh, demonstrates this mechanism. As a consequence of oral administration of a pharmacologically-relevant dose of ethanol, we simultaneously detect a) in the pVTA, a substance untraceable under control conditions, 1-methyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline (salsolinol), product of condensation between DA and ethanol’s first by-product, acetaldehyde, and b) in the AcbSh, a significant increase of DA release. Moreover, such newly-generated salsolinol in the pVTA is responsible for increasing AcbSh DA release via μ opioid receptors (μOR) stimulation. In fact, inhibition of salsolinol’s generation in the pVTA or blockade of pVTA µORs prevents ethanol-increased ipsilateral, but not contralateral, AcbSh DA release. This evidence discloses the long-sought key mechanism of ethanol’s addictive potential and suggests the grounds for developing preventive and therapeutic strategies against abnormal consumption.